The Predicament of Representation in the Politics of Diversity: A Discussion Through Tate Encounters - Honorato, Cayo (Museum and Society, 2020)
Considering the recognition by Arts Council England that cultural diversity within national museums and cultural organizations is ‘treading water’, the article proposes a typology of the criticisms available before putting forward the hypothesis that, no matter how legitimate those criticisms are, most of them are underpinned by an essentialist concept of representation. In order to test this hypothesis, it discusses Tate Encounters, a research project carried out at Tate Britain from 2007 to 2010, as a case study at the intersections of cultural policy and museology, visitor studies and audience engagement. The project provides a situated and multitextured account of the limitations restricting cultural diversity policy. However, it also demonstrates the difficulties in attempting to overcome those limitations – what I call ‘the predicament of representation’. Building upon a post-structuralist perspective, the article understands that, since we cannot escape from representing and being represented, a non-essentialist conception of representation has to be put into practice.